THE ON- AND OFF-STATE GENERATIONS IN CLASSICAL MICROQUASARS. 3-D NUMERICAL HYDRODYNAMICAL SIMULATIONS ON HIGH RESOLUTION GRID IN THE CASE OF INTERMEDIATE MASS TRANSFER RATE IN ACCRETION DISK OF MICROQUASAR CYG X-1 - Nazarenko, V. V. (Одеські астрономічні публікації, 2020)
In the present work we have computed the ON- and OFF-state generations on high resolution grid for microquasar CYG X-1. The results shows that in disk the ON-state time intervals are equal to OFF- state time intervals and these intervals are equal to 2 precession periods. The OFF-states are corresponding to low disk mass accretion rate and ON-states are cor- responding to high disk mass accretion rate. The tran- sition between both states is suddenly, on very short time scale order of 20 minute of orbital time.